Plan de inversión para el mejoramiento de los servicios del instituto computarizado “Laboratorio Siglo XXI C.A.”, cantón Quevedo, Periodo 2014 – 2015 - Loor Manzaba, Jorge Luis (2015)
An investment plan we can describe as "a plan, if you are given a certain amount of capital and will provide inputs of various types, can produce a good or a useful service to society." Research on the investment plan for the improvement of services of the Computer Laboratory Institute Siglo XXI CA, analyzes the market aspects, technical, economic _ financial, and through market research it was established that there is a current demand of 135 people visiting the lab daily. Upon completion of this first part certain current market scenarios were reported. The second part established the technical analysis of the plant on the determination of the location, the same that is located in av. 7 Solar & 12th October No. 4 - 18ava, Quevedo Canton; what size is determined based on the installed capacity and the services they provide, machinery, equipment necessary for the required service. The third part was to condense all the information that monetary previously settled in the technical study, among others, investing $ 725,000.00 total operating costs, working capital, financing 68.97% which is $ 500,000.00 and 31.03% are own contribution will be $ 225,000.00 investors, income statement, net fund flow; in short in this part we tried to obtain all the necessary monetary figures on the economic assessment. At the end of profitability under clearly specified, such as NPV (net present value) $ 15,135.72 and IRR (internal rate of return) 8,345% cost benefit ratio was set 1.65 $ judgments financial indicators demonstrate the feasibility of investment.